PENGUKURAN EFEKTIFITAS SISTEM INFORMASI - Sahfitri, Vivi (JURNAL ILMIAH MATRIK, 2012)
After implementation of IS, required post-implementation review to determine the effectiveness of IS used by looking the influence between variables in measuring the effectiveness of IS. The results of tests performed for variables F Test System Quality, Information Quality and Service Quality to variable Use had no significant effect, while for the t test is performed, the variable does not affect Service Quality significantly Variable on Use. F test on the variable System Quality, Information Quality and Service Quality of Variable User Satisfaction while obtaining significant results for the t test performed, the variable Service Quality variables had no significant effect on User Satisfaction. While the measurements for the F test between the variables System Quality, Information Quality, Service Quality, Use and User Satisfaction variables have a significant Net Benefits among all variables, the t test conducted prove the variable Service Quality no significant effect on the variable Net Benefits Keywords: Efektifitas Sistem Informasi, System Quality, Information Quality, Service Quality, Use, User Satisfaction, Net Benefits